1994
DOI: 10.1002/ajim.4700250505
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological deficit among elderly workers in aluminum production

Abstract: A cross-sectional study was conducted at a Norwegian primary aluminum plant. All workers aged 61-66 years were offered early retirement benefits. Among the workers, 47 met the study criteria and 38 (81%), comprising 14 potroom workers, 8 foundry workers, and 16 controls, volunteered to participate. They were tested with a neuropsychological test battery. Workers in potrooms with Søderberg electrolytic cells were found to show signs of impairment of the nervous system. A test for tremor discriminated significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…The present study was able to reproduce the results of the memory tests only for visual memory, but indeed confirmed the effect on attention. Impaired motor function was suggested for potroom workers in a primary aluminum plant (27) and also among aluminum welders (48). In our study, no effects on psychomotor functions were noted, but it must be kept in mind that few tests were used to explore this domain.…”
Section: Scand J Work Environ Health 2000 Vol26 Nomentioning
confidence: 49%
See 2 more Smart Citations
“…The present study was able to reproduce the results of the memory tests only for visual memory, but indeed confirmed the effect on attention. Impaired motor function was suggested for potroom workers in a primary aluminum plant (27) and also among aluminum welders (48). In our study, no effects on psychomotor functions were noted, but it must be kept in mind that few tests were used to explore this domain.…”
Section: Scand J Work Environ Health 2000 Vol26 Nomentioning
confidence: 49%
“…Qualitatively, previous studies involving foundry work and primary aluminum production (17,26,27) have suggested that a long-term, low-level exposure to aluminum does not deteriorate the general cognitive level estimated by measurements of intelligence quotient, but it may affect performance in tests that are known to be sensitive to diverse disturbances in brain function, including neurotoxic damage (eg, digit symbol and block design). The results of previous studies (17, 26, 3 1) have also indicated the vulnerability of memory and attention.…”
Section: Scand J Work Environ Health 2000 Vol26 Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on workers exposed to Al dust in industrial environments demonstrate similar effects (Rifat, et al, 1990;Bast-pettersen, et al, 1994;White et al, 1992, Akila et al, 1999. Many researchers have found elevated Al levels to be associated with a decline in visual memory, attention, concentration, frontal lobe function and lower vocabulary scores in hemodialysis patients (Bolla et al, 1992).…”
Section: Discussionmentioning
confidence: 89%
“…Hänninen et al (1994) described a decrease in the neuropsychic response, with short-term memory and attention disturbances, and effects on cerebral electric activity at the front of the brain correlated to the Al-s in the 17 shipyard welders with exposure characteristics similar to those in our sample. Bast-Pettersen et al (1994) showed "a suggestion of increased risk of impaired visuospatial organization and tendency to a decline in psychomotor tempo in the potroom workers''. Sjögren et al (1996), with reference to welders exposed to aluminium and manganese, concluded that the observed neurotoxic effects were due to combined exposure to the two metals.…”
Section: Introductionmentioning
confidence: 99%